2015
DOI: 10.1186/s12909-015-0458-3
|View full text |Cite
|
Sign up to set email alerts
|

Supporting culturally and linguistically diverse students during clinical placement: strategies from both sides of the table

Abstract: BackgroundIncreasing proportions of Culturally and Linguistically Diverse (CALD) students within health professional courses at universities creates challenges in delivering inclusive training and education. Clinical placements are a core component of most health care degrees as they allow for applied learning opportunities. A research gap has been identified in regard to understanding challenges and strategies for CALD students in health professional placements.MethodsA key stakeholder approach was used to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
55
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 19 publications
4
55
0
2
Order By: Relevance
“…Several studies show that nursing students from culturally and linguistically diverse (CALD) backgrounds experience the greatest challenges during completion of their clinical placement (Edgecombe, Jennings, & Bowden, ; Mikkonen, Elo, Kuivila, Tuomikoski, & Kääriäinen, ; Mikkonen, Elo, Miettunen, Saarikoski, & Kääriäinen, ; O'Reilly & Milner, ). Nursing students should all receive equal opportunities in education regardless of their backgrounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies show that nursing students from culturally and linguistically diverse (CALD) backgrounds experience the greatest challenges during completion of their clinical placement (Edgecombe, Jennings, & Bowden, ; Mikkonen, Elo, Kuivila, Tuomikoski, & Kääriäinen, ; Mikkonen, Elo, Miettunen, Saarikoski, & Kääriäinen, ; O'Reilly & Milner, ). Nursing students should all receive equal opportunities in education regardless of their backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of this study, having a CALD background means that the student has a native language, cultural background or heritage differing from that of the country where they study. O'Reilly and Milner () found that both mentors and students experienced that the students' cultural and linguistic background had an impact on clinical placements. Mentors and students reported that culture differences have an impact on learning and teaching styles with, for instance difficulties in feedback, self‐directed learning and reflective practices (O'Reilly & Milner, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This internationalization is reflected in the growing numbers of students coming to developed countries to study and train in the healthcare professions (Pitkäjärvi et al . , O'Reilly & Milner ). The greatest challenges encountered by international students participating in healthcare education degree programmes relate to learning experiences during students’ clinical placements (Mattila et al .…”
Section: Introductionmentioning
confidence: 99%
“…). However, as there are also challenges for educators and IS to manage their learning in placements (Harrison and Ip , O'Reilly and Milner ), identifying strategies to facilitate positive experiences may also foster opportunities to realize these potential learning benefits.…”
Section: Introductionmentioning
confidence: 99%